A shrimply amazing tale: a rare case of a perforated Meckel’s diverticulum secondary to a prawn head - Rawther, Thampi; Cecire, Jack; Ooi, Kevin (International Surgery Journal, 2023)
Majority of patients with a Meckels diverticulum remain asymptomatic. However, complications can occur in 4% of patient and tend to present with an acute surgical pathology commonly present with bleeding, obstruction, intussusception or neoplasm. Rarely, people present with a perforation of a Meckel’s secondary to a foreign body. This is an interesting case report of a patient presenting with a perforated Meckel’s secondary to a prawn head. Foreign body perforation of a Meckel’s is quite rare and should be suspected in patients with an acute abdomen, especially in patients with symptoms suggestive of appendicitis. A combination of history, examination and imaging can help narrow the diagnosis. However, a through examination of the small bowel must be performed, especially if the appendix appears normal, to look for a perforated Meckel’s.